Maternal Sevoflurane Exposure Causes Abnormal Development of Fetal Prefrontal Cortex and Induces Cognitive Dysfunction in Offspring - Song, Ruixue (Stem Cells Int, 2017)
Maternal sevoflurane exposure during pregnancy is associated with increased risk for behavioral deficits in offspring. Several studies indicated that neurogenesis abnormality may be responsible for the sevoflurane-induced neurotoxicity, but the concrete impact of sevoflurane on fetal brain development remains poorly understood. We aimed to investigate whether maternal sevoflurane exposure caused learning and memory impairment in offspring through inducing abnormal development of the fetal prefrontal cortex (PFC). Pregnant mice at gestational day 15.5 received 2.5% sevoflurane for 6 h. Learning function of the offspring was evaluated with the Morris water maze test at postnatal day 30. Brain tissues of fetal mice were subjected to immunofluorescence staining to assess differentiation, proliferation, and cell cycle dynamics of the fetal PFC. We found that maternal sevoflurane anesthesia impaired learning ability in offspring through inhibiting deep-layer immature neuron output and neuronal progenitor replication. With the assessment of cell cycle dynamics, we established that these effects were mediated through cell cycle arrest in neural progenitors. Our research has provided insights into the cell cycle-related mechanisms by which maternal sevoflurane exposure can induce neurodevelopmental abnormalities and learning dysfunction and appeals people to consider the neurotoxicity of anesthetics when considering the benefits and risks of nonobstetric surgical procedures.